2013
DOI: 10.1186/1471-2407-13-315
|View full text |Cite
|
Sign up to set email alerts
|

Induction of chromosome instability and stomach cancer by altering the expression pattern of mitotic checkpoint genes in mice exposed to areca-nut

Abstract: BackgroundThere are strong indications for a causal association between areca-nut consumption and cancers. In Meghalaya, India, the variety of areca-nut is used as raw and unprocessed form whose chemical composition and pharmacological actions have been reported. Yet we know little on the initial pathway involved in areca-nut associated carcinogenesis since it is difficult to assess its effects on genetic alterations without interference of other compounding factors. Therefore, present study was undertaken in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Chromosomal instability and heterogeneous gene amplifications/deletions are associated with many malignances [20][21][22][23] . For gastric cancer, Noguchi et al 24 detected no chromosomal deletions of the GSTM1 and GSTT1 genes in their work.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal instability and heterogeneous gene amplifications/deletions are associated with many malignances [20][21][22][23] . For gastric cancer, Noguchi et al 24 detected no chromosomal deletions of the GSTM1 and GSTT1 genes in their work.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mice were given the whole RAN-extract and lime ad libitum in drinking water with dose increased every two months to mimic the human habit of consumption of RAN. In earlier studies with similar mode of treatment, parameters like precocious anaphase and expression of Securin and p53 genes were monitored at different time-points starting from 30 days to 300 days for understanding the process of RAN-induced carcinogenesis 8 . It was found that after 240 days of ad libitum administration of RAN extract with lime in drinking water all the mice developed gastric tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies highlighted the importance of precocious anaphase, which leads to aneuploidy, as a potential screening marker for identification of mitotic checkpoint defects during early days of RAN exposure in both mice and human 8,9,31 . As observed earlier 8 , present results also showed a gradual increase in the frequency of precocious anaphase and aneuploidy in the BMC of mice following RAN + lime administration. Very significantly frequencies of both were reduced following co-administeration of both PRE or ECGU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations